Nontuberculous mycobacteria peri-prosthetic joint infection: An outcome analysis for two stage revision arthroplasty. (17th November 2022) - Peng, Shih-Hui; Lee, Sheng-Hsun; Chen, Chun-Chieh; Lin, Yu-Chih; Chang, Yuhan; Hsieh, Pang-Hsin; Shih, Hsin-Nung; Ueng, Steve W N; Chang, Chih-Hsiang
Purpose: Nontuberculous mycobacteria periprosthetic joint infection (NTMPJI) is a rare complication of hip or knee joint arthroplasty. The experience for outcomes of NTMPJI treatment is still limited. The objective of this study was to investigate the outcome of hip or knee nontuberculous mycobacteria periprosthetic joint infection following treatment with two-stage exchange arthroplasty. Material and Methods: From 1995 to 2020, 12 patients with NTMPJI were treated with two-stage exchange arthroplasty at our institution. We collected and analyzed variables including demographic data, comorbidity, microbiological data, treatment outcome and antibiotic formula in bone cement. Results: Mycobacterium abcessus ( n = 6) and Mycobacterium chelonae ( n = 2) constitute the majority of the cases. Five patients had early-onset PJIs and the other seven patients were late onset. The success rate of two-stage exchange arthroplasty was 66.7% (8 of 12). Three patients experienced infection relapse, and one patient had soft tissue compromise complication. Post-operative antibiotic therapy may not improve the success rate (4 of 6 cases, 66.7%). Based on in vitro study, the most commonly used effective antibiotic in bone cement spacer for nontuberculous mycobacteria was amikacin. Conclusions: nontuberculous mycobacteria is a rare cause of PJIs and should be suspected especially in relatively immunocompromised patients. Resection arthroplasty with staged reimplantation is the preferred approach. Prolonged post-operative antibiotic therapy before reimplantation may not improve the success rate. Delayed revision surgery may not be needed and can be performed once C-reactive protein level is normal after a drug holiday.